Peran Media Pembelajaran Interaktif PATRIKS dalam Meningkatkan Motivasi Siswa - Dewi, Sholehah Kartika; Sulistyono , Bambang Agus; Samijo, Samijo (Polinomial : Jurnal Pendidikan Matematika, 2025)
This research aims to develop an interactive learning media called PATRIKS (Matrix Application) based on PowerPoint and analyse its impact on students' motivation to learn mathematics. The method used in this research employs the R&D (Research and Development) approach with the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The data collection instruments include validation questionnaires from subject matter experts, media experts, practitioners, student responses, motivation instrument experts, and student motivation questionnaires. This research involves students of class XI-7 at SMAN 1 Plemahan as subjects. The research stages include media needs analysis, product design, development and validation by material experts (80% valid) and media experts (99.13% very valid), as well as trials with practitioners (97.4% very practical) and small groups of students (83.69% very practical). The study results indicate a significant increase in student motivation after using the PATRIKS media, with an overall average rising from 61.3% (very low) to 79.1% (moderate). The highest increase was seen in the aspects of desire and aspiration to succeed (from 63.9% to 85.1%), a conducive environment (from 58.8% to 83.3%), and interactivity of the learning media (from 61.3% to 83.3%). Nevertheless, the aspect of perseverance in facing tasks is still relatively low (70.8%) and independence in learning is in the moderate category (75.4%), indicating the need for further development of media features to encourage student perseverance and independence. Overall, the interactive learning media PATRIKS has proven to be valid, practical, and effective in enhancing students' learning motivation, making it a promising educational tool in the digital age.